2018
DOI: 10.3390/s18103426
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Errors in the Estimation of Impact Positions in Plate-Like Structure through the Triangulation Formula by Piezoelectric Sensors Monitoring

Abstract: The structural health monitoring (SHM) of critical structures is a complex task that involves the use of different sensors that are also aimed at the identification of the location of the impact point using ultrasonic sensors. For the evaluation of the impact position, reference is often made to the well-known triangulation method. This method requires the estimation of the differential time of arrival (DToA) and the group velocity of the Lamb waves propagating into a plate-like structure: the uncertainty of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Some linear methods use the propagation of Lamb waves in metal structures [91] with piezoelectric sensor arrays because of their directionality and low dispersion [92]. The propagation of this type of signal is used recurrently in the development of intelligent materials.…”
Section: Excitation Methodsmentioning
confidence: 99%
“…Some linear methods use the propagation of Lamb waves in metal structures [91] with piezoelectric sensor arrays because of their directionality and low dispersion [92]. The propagation of this type of signal is used recurrently in the development of intelligent materials.…”
Section: Excitation Methodsmentioning
confidence: 99%
“…We defined a Region of Interest (ROI) of the aluminum plate equal to 250mm x 240mm (see Figure 1) and this area was divided into a uniform grid of points spaced 1 mm with coordinates (xp, yp) for the following analysis. For each of those points, the impact localization algorithm processed the received signals to extract the differential DTOAs and calculated the value of the error function E(xp, yp) [15][16][17]. Once the error function (1) was calculated for the whole grid, the impact point was assigned by the absolute minimum error value criterion.…”
Section: Impact Detection and Localizationmentioning
confidence: 99%
“…The input attenuator is a fundamental block to adjust for different sensor sensitivity and impact energy. For example, impacts with from 10 mJ to 100 mJ energy can be monitored with 6.5 mm PVDF circular type (see [16] [17]) producing voltage signals in the range of 100mV to 1V, while the highest sensitivity of piezoceramic sensors like Physik Instrumente P-876.SP1 allows signals up to 300 mVpp with the low energy impact hammer or free-falling sphere, typically used during non-destructive laboratory tests. The piezoceramic material of this type of sensors has a high electromechanical coupling factor and high sensitivity.…”
Section: Electronic Instrument Design For Shm Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the triangular method requires only a small number of sensors, which can further reduce resource occupation, but there are also some problems. Taking the flat panel as the research object, the effect of the signal arrival time difference and the Lamb wave velocity on the locating error was analyzed in the triangle method [45]. It is found that the location error of the threshold method is large and unstable.…”
Section: Introductionmentioning
confidence: 99%